An X-Ray Fluorescence and Principal Component Analysis study of pottery from Orraon - Papachristodoulou, C.; Oikonomou, A.; Ioannides, K.; Gravani, K. (HNPS Advances in Nuclear Physics, 2019)
Radioisotope-induced X-ray fluorescence XRF was used to determine the composition of 64 pottery sherds recovered from the settlement of ancient Orraon, northwestern Greece. The XRF data were submitted to Principal components analysis PCA and distinct sample clusters were identified, originating from differences in major and trace elements concentrations. The statistical classification, combined with archaeological criteria, allows conclusions related to the raw materials and paste recipes used in pottery manufacturing. Distinction between local production and imported pottery may also be inferred.